Complement Subordinate Clause Analysis in Complex Sentence Found in CNN Business Online News Article - Dita Nur Rahma; Putu Devi Maharani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study focuses on analysing complement subordinate clauses in complex sentences observed in CNN Business online articles. The aim is to explore how these clauses contribute to sentence structure and meaning in journalistic text. This study uses a descriptive qualitative method. The data were collected from five CNN Business articles published in May 2025 that discuss about tariffs issue involving Donald Trump. Sentence were selected based on the presence of complement subordinate clauses, which were then analysed using Miller’s (2002) theory and illustrated through tree diagrams by Brown and Miller (1991). The findings show a total 18 complement clauses with the highest number of occurrences is 7 data. Most of complement clauses are introduced by complementizer “that” though in some cases it is omitted. The result shows that complement clauses has important role in completing the meaning of the verbs and in forming grammatically coherent complex sentences in writing. Keywords: complement clause, complex sentence, syntax, CNN, tree diagram